1,3-Bis{[5-(pyridin-2-yl)-1,3,4-oxadiazol-2-yl]sulfanyl}propan-2-one - Chao-Hui Xia; Chun-Bo Mao; Ben-Lai Wu (Acta Crystallographica Section E, 2011)
In the distorted W-shaped molecule of the title compound, C17H12N6O3S2, a twofold axis passes through the carbonyl group. The molecules stack in the crystal through π–π interactions [centroid—centroid distance = 3.883 Å] and weak C—H...N hydrogen-bonding interactions, forming a three-dimensional architecture.